Pengaruh Promosi dan Kualitas Pelayanan terhadap Keputusan Pembelian Produk Garam di Tasikmalaya : Sensus pada Pelanggan Garam Pd.Delima di Tasikmalaya 46415 - Wiwit Juwita; Rita Tri Yusnita; Suci Putri Lestari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The purpose of this study was to determine and analyze the effect of promotion and service quality on purchasing decisions for salt products in Tasikmalaya at PD. Pomegranate in Tasikmalaya. The method used in this research is the census method. The population in this study were PD salt customers. Pomegranate in Tasikmalaya. The sampling technique in this study is saturated sampling, so that the entire population in this study is used as the research sample. Based on the results of research and data analysis, it is known that partially the Promotion variable is not significant to Purchase Decision. Service Quality variable is significant to Purchase Decision. Meanwhile, promotion and service quality simultaneously have a positive and significant effect on the decision to purchase salt products in Tasikmalaya at PD. Pomegranate in Tasikmalaya